STUDI EMPIRIS KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG DALAM MEMPENGARUHI NILAI PERUSAHAAN PADA BANK UMUM SWASTA DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIAPERIODE2012-2014 - Hani Sri Mulyani (MAKSI, 2016)
This study has purpose too determine how the effect of Dividend Policy and Debtpolicy to Corporate Value in Private Banks Foreign Exchange that listed in theIndonesia Stock Exchange (BEI) in 2012-2014. Dividend Policy in this research proxyfor Dividend Payout Ratio (DPR), Debt Policy in this study proxied by Debt To TotalAssets Ratio (DAR), and Corporate Value in this study proxied by Price Earning Ratio(PER).The population in this study was 36 Private Banks Foreign Exchange that listed inthe Indonesia Stock Exchange in 2012-2014. The sample in this study consistsof 14companies with purposive sampling method.The method used in this study is Verificative-quantitative. The analysis toolused ismultiple linear regression analysis. The results showed that during the period 2012-2014 Dividend Policy and Debt Policy does not have a significant influence to theCorporate Values.Keywords: Dividend Policy, Debt Policy and Corporate Values.